Integration of Tallu Lolona in the Implementation of Corporate Social Responsibility (CSR) in Micro, Small, and Medium Enterprises (MSMEs) - Felisitas Tandirau; Oktavianus Pasoloran; F.E.Daromes (Cahaya Abadi Publisher, 2026)
Corporate Social Responsibility (CSR) has evolved from a philanthropic activity into a strategic approach to sustainable business, emphasizing the integration of economic, social, and environmental dimensions. In the context of micro, small and medium enterprises (MSMEs), CSR practices are often informal and deeply influenced by local values and community relationships. This study aims to analyze the integration of the Torajan cultural philosophy of Tallu Lolona into the implementation of Corporate Social Responsibility at UMKM Kopi 1000 Nurhidayah and to develop a conceptual model explaining how this integration contributes to business sustainability and community welfare. The research employs a qualitative approach with an interpretive paradigm and a case study method. Data were collected through semi-structured interviews, observation, and documentation involving business owners, employees, local farmers, community members, and local authorities. The findings reveal that CSR is not implemented as a formal administrative program but is embedded in daily business practices rooted in Tallu Lolona, which emphasizes the interconnectedness of humans, plants, and animals. This integration aligns with the triple bottom line framework of people, planet, and profit, resulting in a culturally grounded sustainability model referred to as the Sangkutu’ Banne Model. The study implies that local cultural values can serve as a strong ethical and strategic foundation for CSR in SMEs, enabling contextual, authentic, and long-term sustainability without relying solely on formal reporting systems.